Linking Plant Functional Traits to Demography in a Fragmented Landscape - Portela, Rita de Cássia Quitete; Colmenares-Trejos, Sara Lucía; de Mattos, Eduardo Arcoverde (Frontiers in Forests and Global Change, 2021)
Habitat loss in highly deforested landscapes such as the Brazilian Atlantic Forest has been severely affecting the diversity and survival of palm species. As some species are more sensitive than others, trait responses to the environment, as well as environmental effects on fecundity, growth, and mortality rates, may affect species demography. Considering this context, we studied functional and demographic responses of three palm species (Astrocaryum aculeatissimum, Euterpe edulis, and Geonoma schottiana) to habitat loss in the Atlantic Forest in southeastern Brazil by measuring morpho-physiological traits related to plant growth and light acquisition for photosynthesis. We also tested the response of population fitness to fragment size. Plant survival and growth was subsequently monitored in 2006 and 2007, and population dynamics were summarized in pool matrices for large and small forest fragments in the monitoring periods comprehending one full year between 2005–2006 and 2006–2007. The asymptotic growth rate of populations (defined here as population fitness, λ) in five forest fragments was then calculated. Diameter of individuals of the demography plots (from year 2005 to 2007) was used to calculate the relative diameter growth rate. Later, in 2015, we measured a set of morpho-physiological functional traits in palms in the same plots used in the demographic studies. While A. aculeatissimum populations were stable in both monitoring periods in small and large fragments, E. edulis populations were predicted to decline due to intense predation by monkeys in the large fragment, but were stable in the smaller fragments, and G. schottiana populations were stable in the large fragments in both monitoring periods, but populations in the smaller fragments were predicted to decline in the second period, i.e., with lower fitness in these fragments. In addition, the functional traits analyzed showed that G. schottiana is a forest interior species associated with the shade/understory environment response. E. edulis was also affected by the size of the fragment, but due to a disruptive interaction with a predator and showed intermediate functional traits values. On the other hand, A. aculeatissimum thrived in areas with higher and lower incidence of light and was not demographically affected by forest remnant size. This suggests that E. edulis and A. aculeatissimum are habitat generalists. We concluded that differences in the ecophysiological performance of palms due to distinct morpho-physiological functional traits related to leaf economic spectrum, such as LDMC or specific leaf area (SLA) and to photosynthetic responses to light environment as electron transport rate (ETR) and saturation irradiance (Ik) were linked to the demographic variation observed in forest remnants of different size.